Willow: Leaves, wood and bark: Problems of growth and differentation - Kefeli, V.; Leininger, C.; Rehn, B.; Shwarz, K. (İstanbul Kültür Üniversitesi, 2008)
The growth of woody plants as perennial organisms is based on the long lasting process of organs elongation and differentiation. This process proceeds on rhythmic activity of plant meristems and cambium formation. The growth is succeeded by wood and bark differentiation as well as carbon polymers formation (mostly cellulose, starch and lignin). These secondary substances are formed from the primary products of photosynthesis. Roots also play an important role of stem elongation and leaves formation. In our experimental work we investigated such basal processes as leaves growth; growth and differentiation of stems and roots regeneration.
Keywords: Growth; differentiation; regeneration; rhythms; wood-bark; büyüme; farklılaştırma; ritimler; odun-kabuk